Uji Daya Hasil Pendahuluan dan Mutu Beras 21 Padi Hibrida Harapan - Lestari, Angelita Puji; Aswidinnoor, Hajrial; Suwarno, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Preliminary Yield Trials and Grain Quality of 21 Promising Hybrid Rice. Hybrid rice varieties are alternative technology for increasing national rice productivity.  Heterosis effect from the hybrid F1 can increase yield potential 15% more than inbred rice varieties. The objectives of this experiment were to test the yield and rice quality of some hybrid rice varieties, compared with the three check varities i.e. IR64, Memberamo, and Maro. This experiment was conducted at Muara Experimental Farm, Bogor during wet season 2002/2003 (December-May). A Randomized Complete Blocked Design in three replications was used for this experiment. The result shows that the yield of hybrid rice combinations H-27, H-28, H-29, H-30, H-31, H-32, H-35, H-37, H-38, H-39, H-40, H-41, H-42, H-43, H-45, H-47, H-48 had short growth duration and have erect leaf appearance, but most of them had less resistance to pests and diseases caused by bacteria, and low percentage of grain content. The yield of these hybrids except H-27 and H-49 were lower than the check varieties and all of the hybrid rice tested in this experiment were good in terms of cooking quality. H-27, H-30, H-34, H-41, H-45 dan H-49 could be tested in the advance yield trials.   Key words: hybrid rice, preliminary yield, grain quality